2009
DOI: 10.1111/j.1473-6861.2008.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

The art therapy large group as a teaching method for the institutional and political aspects of professional training

Abstract: This paper discusses a unique experiential teaching method in the context of training for art psychotherapists and raises issues relevant to teaching for all workers in health and social care. The art therapy large experiential group of all the students and all the staff (80+), which is held six times a year on the 2-year full-time/3-year part-time programme, is identified with three educational components: learning about art therapy processes, learning about the educational process of becoming a professional,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Our previous theory (Skaife and Jones, 2009; Skaife, Jones and Pentaris, 2016) spoke of specific learning outcomes for the ATLG. Our research has shown that we cannot know what a learning outcome will be prior to any group or session taking place, it has to be found, or re-found each time.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous theory (Skaife and Jones, 2009; Skaife, Jones and Pentaris, 2016) spoke of specific learning outcomes for the ATLG. Our research has shown that we cannot know what a learning outcome will be prior to any group or session taking place, it has to be found, or re-found each time.…”
Section: Resultsmentioning
confidence: 99%
“…This mind/body split they thought, reflected other hierarchical binaries, for example, in class, race and gender. Skaife and Jones (2009) illustrated this with a case example of a post group in which the male staff favoured cognitive interpretation and the female staff the aesthetic process. They describe how this large group enactment made the artificial split visible.…”
Section: Part Onementioning
confidence: 98%
See 3 more Smart Citations